Terras (Eusideroxylon zwageri Teijsm. & Binn.), a Cultural Keystone Species of the Berawan People of Sarawak, Malaysia - Franco, F; Ghani, B.A.A.; Hidayati, S. (Universiti Putra Malaysia Press, 2014)
This article showcases the unique position accorded to the terras tree (Eusideroxylon zwageri Teijsm. & Binn. Lauraceae) in the Berawan culture. We collaborated with the Berawan people of the Loagan Bunut region of Sarawak, to uncover the most important tree in their culture. In a group interview, the participants ranked the terras as the most important tree. The Identified Cultural Influence of Cultural Keystone Species (ICI) and the Use Value Index (UV) was found to be extraordinarily high at 35 and 6.05 respectively. The multidimensional use value of the tree, stemming from its hardy timber, could be the reason behind its cultural importance. We conclude that the terras tree should be protected even outside the national parks for its ecological and cultural value.